Solar-blind ultraviolet photodetector based on (LaAlO3)0.3-(SrAl0.5Ta0.5O3)0.7 single crystal - Jian-yu Du; Chen Ge; Jie Xing; Jian-kun Li; Kui-juan Jin; Jing-ting Yang; Hai-zhong Guo; Meng He; Can Wang; Hui-bin Lu; Guo-zhen Yang (AIP Advances, 2017)
A solar-blind ultraviolet photodetector based on perovskite (LaAlO3)0.3-(SrAl0.5Ta0.5O3)0.7 (LSAT) single crystal has been fabricated. The Deep Ultra Violet (DUV)/Ultra Violet (UV) (200 versus 290 nm) ratio is more than three orders of magnitude under the applied bias voltage 200 V. Under illumination at 200 nm, the responsivity of this ultraviolet photodetector reaches 4 mA/W at 200 V bias. The corresponding quantum efficiency and detectivity are 2.76% and 1×1011 cm⋅Hz0.5/W, respectively. The ultrafast response with a rise time of 563 ps and full width half maximum (FWHM) of 1.085 ns is obtained. The high sensitivity, ultrafast response speed, and good signal-to-noise ratio demonstrate that the LSAT photodetector could be a promising candidate as the solar-blind ultraviolet photodetector.